Failure Mechanism and Control of Lower Retracement Channel in Close-Distance Double-Thick Coal Seams. (27th February 2021) - He, Fulian; Lv, Kai; Li, Xiaobin; Qin, Binbin; Li, Liang
Abstract : Under the condition of close-distance double-thick coal seams' mining, the serious strata behavior occurred in the lower retracement channel, which is affected by the double disturbance with upper coal-pillar static load and mining dynamic pressure. Field investigation, laboratory test, and numerical simulation were used to study the failure characteristics and stress distribution of N0381 retracement channel. The results show that the plastic failure and stress of the surrounding rock are obviously asymmetric; specifically, the closer the roof is to N0381 gob, the stronger the strata behavior is. In addition, when the upper coal pillar is in critical stable or stable state (w / h > 2 ), high stress concentration in the upper coal pillar is transmitted downward through floor rock so that two dangerous areas with severe strata behavior are formed in N0381 retracement channel. In view of this, a partition control strategy with "high-pressure water jet + asymmetric high-strength cable-beam net + three-hole anchor cable group + roof grouting" as the core is proposed to ensure the stability of the lower retracement channel. This study provides a reference for coal mines with similar production geological conditions.